2020
DOI: 10.1186/s12871-020-0956-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low versus standard pressure pneumoperitoneum on renal syndecan-1 shedding and VEGF receptor-2 expression in living-donor nephrectomy: a randomized controlled study

Abstract: Background Laparoscopic nephrectomy is a preferred technique for living kidney donation. However, positive-pressure pneumoperitoneum may have an unfavorable effect on the remaining kidney and other distant organs due to inflamed vascular endothelium and renal tubular cell injury in response to increased systemic inflammation. Early detection of vascular endothelial and renal tubular response is needed to prevent further kidney injury due to increased intraabdominal pressure induced by pneumoperitoneum. Transpe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…34 In laparoscopic nephrectomy, Dita Aditianingsih et.al demonstrated an attenuation of the in ammatory response, including IL-6, in the low-pressure pneumoperitoneum group (8 mmHg) compared to standardpressure (12 mmHg). 35 In conclusion, this clinical trial demonstrated a reduction of pain and in ammatory markers post laparoscopic cholecystectomy in patients operated at a low-pressure (8-10 mmHg) compared to a standard-pressure (12-14 mmHg), although the difference was not signi cant except for the 6-hour postop pain scores. No signi cant difference could be observed between the two groups regarding total surgery time, also the di culty of surgery was not signi cant even in the hands of non-experienced surgeons.…”
Section: Discussionmentioning
confidence: 65%
“…34 In laparoscopic nephrectomy, Dita Aditianingsih et.al demonstrated an attenuation of the in ammatory response, including IL-6, in the low-pressure pneumoperitoneum group (8 mmHg) compared to standardpressure (12 mmHg). 35 In conclusion, this clinical trial demonstrated a reduction of pain and in ammatory markers post laparoscopic cholecystectomy in patients operated at a low-pressure (8-10 mmHg) compared to a standard-pressure (12-14 mmHg), although the difference was not signi cant except for the 6-hour postop pain scores. No signi cant difference could be observed between the two groups regarding total surgery time, also the di culty of surgery was not signi cant even in the hands of non-experienced surgeons.…”
Section: Discussionmentioning
confidence: 65%
“…The anaesthetic and physiological implications of lower pressure pneumoperitoneum have been demonstrated by multiple studies. These include reduced lactate levels and more favourable cytokine responses [ 17 – 21 ]. These findings have a presumptive benefit, however, how they translate to reduced complication rates and reduced morbidity and mortality is to date undemonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Renal circulation is greatly affected by increased intra-abdominal pressure, and measurement of kidney injury biomarkers shows significant changes during pneumoperitoneum with a positive correlation with pressure levels [ 8 ]. A change in renal blood flow was suggested in a meta-analysis conducted by Wever et al, although the authors highlight the low quality of the evidence, the need for further studies to clarify the issue, and the fact that only animal studies were included [ 9 ].…”
Section: Discussionmentioning
confidence: 99%